Meningoencephalitis Due to Listeria monocytogenes in a Pregnant Rhesus Macaque (Macaca mulatta) - Lemoy, Marie-Josee MF (American Association for Laboratory Animal Science, 2012)
We here report a spontaneous case of meningoencephalitis due to Listeria monocytogenes in an adult primiparous rhesus macaque (Macaca mulatta) during an outbreak of listeriosis in an outdoor enclosure. Clinical signs included tremors, abnormal posture, and altered mental status. Hematology and analyses of cerebrospinal fluid were consistent with bacterial infection. Pure cultures of L. monocytogenes were recovered from the placenta–abortus, cerebrospinal fluid, and brain tissue. The macaque did not respond to treatment and was euthanized. Histopathologic examination of the brain revealed acute meningoencephalitis. This case represents an unusual clinical and pathologic presentation of listeriosis in a nonhuman primate in which the dam and fetus both were affected.